PRODUCTION AND CHARACTERIZATION OF COMPOSITE POWDER FROM MEDIUM ENTROPY ALLOYS PRODUCED USING W, Mo, Nb – Fe, Ni, Co POWDERS - Albayrak, Muhammet Gökhan (My University, 2025)
Todays, Middle Entropy Alloys (MEA) are a relatively new production method and have extraordinary advantages over classical methods. The biggest advantage is defined as the production of complex compounds that cannot be combined with known methods. MEAs prepared with transition metals such as Fe, Ni, Co have an important place due to their superior properties such as anti-oxidation, corrosion and wear behavior. Metals with refractory properties such as W, Mo, Nb are interesting due to their high hardness as well as high temperature applications. In this study, which aims to characterize two different MEA powders produced, MEA powders were produced using refractory metals such as W, Mo and Nb and transition metal powders such as Fe, Ni and Co. The difference of this publication is that all powders are not brought together at once during production, but W, Mo, Nb and Fe, Ni, Co powders are produced separately and combined later. Mechanical Alloying (MA) was preferred as the production method due to its advantages such as reducing grain size and ensuring chemical homogenization. XRD, SEM and EDS (mapping) analyses were performed for the characterization of the obtained medium entropy alloy composite. Thanks to the MA technique, the powder sizes were reduced and both MEA powders were successfully distributed homogeneously within each other.
Keywords: Characterization; FeNiCo; complex compounds; middle entropy alloy; WMoNb